Adoption of Customary Land Tenure as a Model in Agrarian Reform: A Study of the Tenurial System in Tenganan Pegringsingan Village - Destriananda Safa Aina; Pertiwi, Putri; Minasta, Muh Faqihuddin; Rahmawati, Bolivia; Sari, Almonika Cindy Fatika (BHUMI: Jurnal Agraria dan Pertanahan, 2024)
Abstract: The high frequency of agrarian conflicts involving customary land reflects the weak legal protection of communal land rights. In response, the government issued Presidential Regulation Number 62 of 2023 concerning the acceleration of agrarian reform implementation, aimed at providing legal protection for customary land through land legalization and redistribution programs. However, the program's implementation has been ineffective due to the limited recognition of communal land rights, which does not fully prevent the repurposing of legalized customary land for investment or commercial use. As a comparison, Tenganan Pegringsingan Village in Bali demonstrates a robust system of customary land tenure, where land remains protected from conversion despite significant tourism pressures. This article aims to explore the values within the customary land tenure system in Tenganan Pegringsingan and its potential integration into agrarian reform agendas. This study employs a socio-legal approach, with data collected through non-participatory observation and in-depth interviews. The findings reveal that some aspects of the customary land tenure in Tenganan align with the principles of agrarian reform, while others do not, primarily due to the influence of modernization, tourism, and the role of tenant farmers. However, this village's customary land tenure system presents a novel model for agrarian reform initiatives in similar communities. Keywords: Agrarian Reform, Customary Law, Tenganan Pegringsingan